(untitled) (Journal of Eye Movement Research, 2016)
The purpose of this study was to investigate the effect of optically induced refractive errors on saccade latency and fixation stability. Sixteen healthy, young adults (two males), with normal visual acuity and normal accommodation, performed a saccade task and a fixation task wearing a range of contact lenses (from +3.00 to -5.00 diopters) which induced visual blur and accommodation. The results showed that mean (± standard error) saccade latency was 207 (± 5) milliseconds (ms) and remained stable with both visual blur and accommodation, whereas mean (± standard error) fixation stability was logBCEA 2.48 (± 0.03) (arcmin²) and declined by about 0.09 logBCEA with both visual blur and accommodation. In healthy adults with normal vision, results indicate that recording of saccade latency can be completed accurately regardless of the moderate refractive errors induced in this study. Fixation stability, on the other hand, degrades slightly with blur and with accommodation.